An achievement test in Pilipino for grade six Cebuano learners - Sandalo, Myrna Mission 1946- (s.n.], 1972)
An achievement test in Pilipino for Grade VI Cebuano learners was constructed and evaluated in this study. An original 200-item test based on a Table of Specifications was administered to 400 Grade VI pupils in the Division of Agusan del Norte. Results showed that the proposed achievement test is linguistically-valid and highly reliable. The liguistic difficulties of Cebuano learners of Pilipino were revealed in the study but have not yet been overcome to a satisfactory level.